2000
DOI: 10.1074/jbc.275.10.6798
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Characterization of Biotin Sulfoxide Reductase

Abstract: Resonance Raman spectroscopy has been used to define active site structures for oxidized Mo(VI) and reduced Mo(IV) forms of recombinant Rhodobacter sphaeroides biotin sulfoxide reductase expressed in Escherichia coli. On the basis of 18 With the exception of nitrogenase, molybdenum enzymes catalyze formal oxygen atom transfer between water and substrate and contain an active site in which the molybdenum is coordinated by the dithiolene side chain of one or two molybdopterins (Fig. 1a) (1-3). Although the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
(105 reference statements)
4
29
0
Order By: Relevance
“…Reduction with Me 2 S-Whereas the ability of DMSOR to be reduced by Me 2 S has been studied extensively using various techniques (11,15,17), BSOR cannot be reduced by either Me 2 S or biotin (16), and the activity of TMAOR upon product addition has not been studied previously. To investigate how mutation of Tyr-114 alters this activity, data were obtained as described by Adams et.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reduction with Me 2 S-Whereas the ability of DMSOR to be reduced by Me 2 S has been studied extensively using various techniques (11,15,17), BSOR cannot be reduced by either Me 2 S or biotin (16), and the activity of TMAOR upon product addition has not been studied previously. To investigate how mutation of Tyr-114 alters this activity, data were obtained as described by Adams et.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are some shifts in the cycled Mo(VI) absorption spectra of the mutants at longer wavelengths, all of the main features seen for the wild-type proteins still remain, indicating that the molybdenum coordination environments are similar. Resonance Raman studies have indicated that the absorption peak at 550 nm is associated with the Mo-O bond found in the hexa-coordinate, mono-oxo spectra (15,16). This absorption peak is changed very little from wild type in either of the Tyr mutants, and it does not appear that the presence or absence of this Tyr greatly perturbs the catalytic Mo-oxygen , and molybdenum concentration was determined using atomic absorption spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations